Primary Mathematical Modeling of the Growth of SDS by a bacterium Isolated From a Paddy Field (Journal of Environmental Microbiology and Toxicology, 2024)
The maximum specific growth rate and other critical parameters can be obtained from the mathematical modelling of microbial growth on toxic cubstances using nonlinear regression of several models. These models form the basis for secondary modelling in predictive microbiology. NumerousiImportant biotechnological applications like bioremediation and wastewater treatment rely on models that explain how substrates affect bacterial growth and biotransformation processes. These models include the modified Gompertz, modified Logistic, modified Richards, Buchanan-3-phase, Baranyi-Roberts, modified Schnute, von Bertalanffy, Morgan-Mercer-Flodin (MMF), and Huang. A previously isolated SDS-degrading Pseudomonas sp. strain Maninjau1 was studied for its growth on SDS using these primary models. Experimental data showed that SDS concentrations from 0.25 to 2.2 g/L (250 to 2200 mg/L) were toxic, slowing bacterial growth. As SDS concentrations increased, toxicity was evident, marked by an increase in the lag phase from 5.9 to 6.9 hours and a decline in biomass. The highest growth rate was observed at 1000 mg/L SDS. The bet model based on error function discriminatory analysis is MMF, which outperformed other models that were tested. The reasons for this include a favorable accuracy (AF) and bias factor (BF), a low root-mean-square (RMSE) and AICc value, and a high adjusted coefficient of determination. The validity of the MMF model for simulating bacterial development in toxic environments is supported by its high reliability. Insights into how bacteria adapt and grow under stressful circumstances can greatly improve biotechnological processes.
Keywords: Primary models; Biodegradation; SDS; MMF model; Pseudomonas sp.